An Analytical Model of Quadrotor Electrical Energy Consumption - Honcharenko, Vadym; Yesilevskyi, Valentyn (Engineering, Technology & Applied Science Research, 2026)
The electrical energy consumption of a quadrotor is a critical factor limiting mission duration. Existing models rely on experimental data for specific configurations or simplify the underlying processes, limiting generalization and accuracy. This study presents a generalizable and accurate analytical model for estimating the electrical energy consumption of a quadrotor based solely on manufacturer-provided parameters, without requiring additional parameter identification or aerodynamic assumptions. The model integrates a second-order Thevenin battery equivalent circuit, an Electronic Speed Controller (ESC), and a first-order motor model that accounts for nonlinear voltage drop effects and load-dependent efficiency. Model input variables are limited to rotor angular speed and torque, and all model parameters are known component specifications. The model decouples energy estimation from aerodynamic models, enabling integration into various simulations and control systems. Simulation results demonstrate that the proposed model produces more accurate results than simplified models, allowing for a reduction of up to 21% relative to a constant-voltage baseline, and it matches motor-current curves from public bench measurements. The model offers practical benefits for UAV mission planning, energy-aware control algorithms, and research on drone endurance optimization.